2011
DOI: 10.2174/1874073101105010001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ischemia Drugs have no Effect on the In Vivo Metabolism of ATP by RBC in Normotensive Restrained Rats#

Abstract: Abstract:The objective is to determine the effect of anti-ishemia agents on metabolism of adenosine-5'-triphosphate (ATP) in red blood cell (RBC) in a normotensive rat model. Male Sprague Dawley (SD) rats weighing between 300 -400 g were used. Each rat received either saline (control), or 5 mg/kg of diltiazem (DTZ), losartan, amlodipine or dipyridamole by subcutaneous injection (sc) twice daily for 5 doses. Blood samples were collected using a "Stopping Solution" from each rat at time 0 (before the last dose),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It has been suggested that ATP catabolism in the RBC may be used as biomarker to quantify myocardial and endothelial ischemia [ 1 , 52 ], and as a potential target for anti-ischemia drugs [ 54 , 55 , 56 , 57 , 58 ]. We hypothesize agents which preserve ATP concentrations in the RBC would have protective effects against ischemia and/or cardiovascular injury [ 90 ].…”
Section: Biomarker and Target For Development Of Drug Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that ATP catabolism in the RBC may be used as biomarker to quantify myocardial and endothelial ischemia [ 1 , 52 ], and as a potential target for anti-ischemia drugs [ 54 , 55 , 56 , 57 , 58 ]. We hypothesize agents which preserve ATP concentrations in the RBC would have protective effects against ischemia and/or cardiovascular injury [ 90 ].…”
Section: Biomarker and Target For Development Of Drug Therapymentioning
confidence: 99%
“…Based on the definition proposed by the FDA Biomarker Definition Working Group [ 51 ], a “Biomarker is a characteristic that is objectively measured and evaluated as an indicator of normal biological processes, pathogenic processes, or pharmacologic responses to a therapeutic intervention”. It has been suggested ADO and ATP catabolism may be used as biomarkers to quantify myocardial and endothelial ischemia [ 1 , 52 , 53 ], cardiovascular toxicities [ 43 ], and as a potential target for anti-ischemia drugs [ 54 , 55 , 56 , 57 , 58 ]. On the other hand, exercise has been shown to improve cardiovascular hemodynamic and increase RBC concentrations of ATP in both humans and animal models [ 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the hemodynamic effect, DTZ also decreased concentrations of ADP and AMP significantly in the RBC ( p < 0.05) and modestly increased ATP concentration ( p > 0.05) ( Table 1 ) in the rats prior to receiving isoproterenol. We have shown earlier that DTZ also increased RBC concentrations of ATP in a zebrafish model [ 23 ] and in an exercise rat model [ 24 ], but not in rats kept in a restrainer [ 25 ]. The results suggest that the effect of DTZ on ATP metabolism in RBC in vivo may be enhanced when energy demand increases in the host species, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of adenosine is very short lived because it is rapidly taken up by myocardial and endothelial cells, red blood cells (RBC), and also rapidly metabolized to inosine and subsequently to hypoxanthine, adenine, S-adenosyl homocysteine (SAH), and other adenine nucleotides [8,18,44,45]. In our laboratory, we have been studying the potential of circulatory concentrations of adenosine and ATP, and their metabolites as biomarkers for cardiovascular protection and as targets for anti-ischemia drugs for several years [46][47][48][49]. It has been postulated that adenosine and ATP may be used as sensitive biomarkers to quantify myocardial and endothelial ischemia [8,44,50], and for monitoring therapeutic effects of anti-ischemia drugs [46,48,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that adenosine and ATP may be used as sensitive biomarkers to quantify myocardial and endothelial ischemia [8,44,50], and for monitoring therapeutic effects of anti-ischemia drugs [46,48,[51][52][53]. More recently, we have shown that exercise improves cardiovascular hemodynamic and increases RBC concentrations of ATP and guanosine 5'-triphosphate (GTP) in a rodent model, particularly in the rats pre-treated with diltiazem (DTZ) [47,54,55], which was not observed in non-exercise rats [49]. The increase of circulatory concentrations of adenosine and ATP could be key factors for exercise preconditioning and a mechanism responsible for cardiovascular protection [17,34,56,57].…”
Section: Introductionmentioning
confidence: 99%